Kualitas Pelayanan Publik dalam Pemberian Izin Mendirikan Bangunan Di Badan Pelayanan Perizinan Terpadu - Andy Frans Leo Silalahi; Syafruddin Ritonga; Beby Masitho Batubara (Universitas Medan Area, 2019)
This research title is ”Services Building Permit in Achieving Optimal Quality Public Services are held at Integrated Licensing Service Agency Pematang Siantar”. So far, in the minds of the public, that the quality of service Building Permit less bureaucracy and process sounds a bit complicated, and less than optimal. The main problem in this research is how the quality of public services in the granting of building permit in the Integrated Licensing Service Agency Pematang Siantar. The methods of data collection to use in this research were kuesioner, observation and documentation. The results showed that the quality of public services in the Service Agency of Integrated Licensing Pematang Siantar has been running well although there are still some constraints. This research uses the service quality theory of Zeithaml, Parasuraman and Berry consisting of 5 indicators of service quality that is tangible (physical evidence), reliability, responsiveness, Assurance and Emphaty. The survey results obtained from the respondents are tangible (physical evidence) of 51.9% (Pretty Good), Reliabelity of 77.2% (Good), Responsiveness of 73,4% (Good), Assurance 65,8% (Good), and Emphaty of 60,76%(Good). From these indicators can be concluded that the quality of service in the Integrated Licensing Service Agency Pematang siantar included in good category